2017
DOI: 10.1161/hypertensionaha.117.09482
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Control in Adults With Diabetes Mellitus and Recurrent Cardiovascular Events

Abstract: Systolic blood pressure (SBP) treatment targets for adults with diabetes remain unclear. SBP levels among 12,275 adults with diabetes, prior cardiovascular disease, and treated hypertension were evaluated in the TECOS randomized trial of sitagliptin vs. placebo. The association between baseline SBP and recurrent cardiovascular disease was evaluated using multivariable Cox proportional hazards modeling with restricted cubic splines, adjusting for clinical characteristics. Kaplan-Meier curves by baseline SBP wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Thus, diabetic patients with BP values near the upper limit of normal should be monitored for the development of hypertension, especially if they have a positive family history of hypertension and the phenotypic features of the metabolic syndrome. Since development of hypertension in patients with diabetes is marked by a significant increase in macrovascular and microvascular risk 2, 23 , efforts should be made to delay or ideally prevent the increase in BP. Obviously, the follow-up scheme of both MCDS and FOS does not reflect everyday clinical practice, as is generally true of observational population-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, diabetic patients with BP values near the upper limit of normal should be monitored for the development of hypertension, especially if they have a positive family history of hypertension and the phenotypic features of the metabolic syndrome. Since development of hypertension in patients with diabetes is marked by a significant increase in macrovascular and microvascular risk 2, 23 , efforts should be made to delay or ideally prevent the increase in BP. Obviously, the follow-up scheme of both MCDS and FOS does not reflect everyday clinical practice, as is generally true of observational population-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…155 Recent data suggest a U-shaped relationship between BP and cardiovascular outcomes in T2D, where systolic BP over 150 mmHg or less than 110 mmHg portends a poorer prognosis. 156 Maintenance of BP within this range appears to be the most appropriate strategy in T2D. In view of these and other large prospective studies evaluating BP-lowering targets in DM, current National Institute for Health and Care Excellence (NG28) recommendations are that BP be maintained below 140/80 mmHg in uncomplicated T2D or below 130/80 mmHg if there is a history of kidney, eye or cerebrovascular disease.…”
Section: Pharmacological Interventions To Reverse Cardiovascular Dysfmentioning
confidence: 99%
“…However, patients with more than one cardiovascular event were not reported separately [ 8 ]. Observational data from two recent trials of inhibitors of dipeptidyl-peptidase 4 have revealed U-shaped relationships between SBP and adjusted CVD rates in patients with type 2 diabetes and established cardiovascular disease or multiple risk factors [ 9 , 10 ] but did not evaluate the risk of death. In patients with diabetes and high cardiovascular risk who participated in the ONTARGET/TRANSCEND (Ongoing Telmisartan Alone and in Combination with Ramipril Global Endpoint Trial/Telmisartan Randomised Assessment Study in Angiotensin Converting Enzyme Inhibitor Intolerant Subjects with Cardiovascular Disease) trials, on-treatment SBP less than 120 mmHg was associated with higher risk for cardiovascular events and for death, but that study excluded patients with symptomatic heart failure [ 12 ].…”
Section: Discussionmentioning
confidence: 99%